2021
DOI: 10.3992/jgb.16.4.81
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pv Powered Switchable Glazing Technologies in Terms of Their Suitability for Office Windows in Moderate Climates

Abstract: In the search for façade solutions that meet requirements for energy efficiency and office space use comfort, it seems promising to apply a combination of photovoltaic (PV) technology with switchable glazing. It is believed that the merging of these two technologies might benefit the cooperation between regulated solar protection and energy efficiency. This article provides a design outlook on the use of PV-EC, PV-SPD, and PV-LCD technologies in terms of their utility for office buildings in moderate climates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…On the other hand, the negative attitude increases if employees are given the possibility of individual device regulation. This result may likely contradict the thesis that the office user is willing to directly impact the workplace environment shaping [29]. However, additional research, i.e., into the correlations between answers to questions 13 and 14 (see Section 3.2.5), reveals a slightly different outlook.…”
Section: Overall Results-collective Answersmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the negative attitude increases if employees are given the possibility of individual device regulation. This result may likely contradict the thesis that the office user is willing to directly impact the workplace environment shaping [29]. However, additional research, i.e., into the correlations between answers to questions 13 and 14 (see Section 3.2.5), reveals a slightly different outlook.…”
Section: Overall Results-collective Answersmentioning
confidence: 90%
“…In this aspect, perovskite- [27], DSSC- [28], and organic cells [20] are investigated. Together with the second-generation thin-film cells, they offer new possibilities, as they may be combined with other technologies, such as switchable glazing [29]. Moreover, creating innovative material and construction solutions, such as joining PV cells with timber [30] or ETFE foil [31], has become possible.…”
Section: State-of-the Artmentioning
confidence: 99%
“…Switchable glazing plays the main role of a responsive sun barrier, whereas the Pv is the electricity generator required to power the glazing. Additionally, PV can play an auxiliary role in the solar protection of rooms (Marchwiński, 2021b). Future cooperation is expected mainly with the use of electrochromic glazing (Huang et al, 2016) but also with SPD (Gosh & Norton, 2019).…”
Section: Hybrid Solutionsmentioning
confidence: 99%
“…In individual applications, i.e., their SBS configuration, the transition to the complete darkening phase takes from a few to about 20 minutes, with the phase change span being directly proportional to the glazing area. It is the longest transition time among all switchable glasses [2].…”
Section: Utility and Energy Behaviormentioning
confidence: 99%
“…Solar cells that generate electricity from sunlight are considered a solution with which to support the work of switchable glazing, to make it self-sufficient in energy terms , thus in line with the idea of shaping energy-saving architecture. The extensive analysis of the PV-switchable technology conducted earlier by the author revealed that, at present, the use of electrochromic glazing is most advantageous in the construction application context [2]. One of the advantages lies in no need for electric current conversion -both technologies operate on direct current, which reduces the need for inverters.…”
Section: Introductionmentioning
confidence: 99%